Associations of Opium Use with Metabolic Syndrome in Fasa PERSIAN Cohort Study: A Population-Based Study - Rafat Shadmehr; Mehdi Sharafi; Mohammadhossien Shahabzadeh; Mostafa Bijani; Rahim Sharafkhani; Babak Pezeshki; Abdolmajid Ghasemian; Azizallah Dehghan (International Journal of Preventive Medicine)
Background: This study aimed to determine the relationships between opium use and metabolic syndrome in Fasa PERSIAN cohort data. Methods: This was an analytical cross-sectional study conducted among participants of the first phase of the Fasa PERSIAN cohort study. A total of 10,074 participants (aged 35–70 years) were studied. The MetS was defined as per the National Cholesterol Education Program ATP III (NCEP-ATP III) criteria. Independent sample t-test and Chi-square test were used for univariate analysis, and multivariate logistic regression was used to control for potential confounders and calculate odds ratios (ORs). Results: The MetS prevalence was 24.6% in the whole population (28.42% in women vs. 19.94% in men, P < 0.001). The prevalence of opium use was 23.2%. The odds of metabolic syndrome in smokers was lower than in non-smokers (OR = 1.17%, 95% CI 1.001–1.37). Conclusions: The results of this study showed that opium consumption has an inverse relationship with metabolic syndrome. However, this study was cross-sectional, and longitudinal studies are needed for more accurate conclusions. Opium is also a carcinogen. Therefore, its use is not recommended.